Structure and wear resistance of aluminium alloys coated with surface layer laser-modified by silicon carbide - Student, Mykhaylo; Pokhmurska, Hanna; Zadorozhna, Khrystyna; Dzyubyk, Andrii; Khomych, Ivan (Lviv Politechnic Publishing House, 2018)
Modern approaches to ensuring the necessary characteristics of surface of a material with the aim to improve economic and technological characteristics of the structures are considered in this paper. It is shown that aluminium alloys gain wide application in industry. Nevertheless, surface characteristics of materials are insufficiently good for their use in structures which operate under abrasive wearing and boundary friction. The use of the method of surface modification by a concentrated light-beam of energy is of prospect. Analysis of literature data indicates that in the course of laser-modification of surface of an aluminium alloy it is possible to form a material whose operational characteristics are higher than those of the material in its initial state. However, herewith it is important to quantitively estimate properties of the obtained composite layer on the surface of the article as well as to estimate the distinction between the layer and the main metal. The microstructure of laser-modified composite layers of aluminium alloys which had been formed by means of direct blow-in of SiC powder into the melted by laser radiation zone of surface has been investigated. Laser reinforcement of surfaces of aluminium alloys by SiC particles causes pronounced inhomogeneity of structure of surface layers of alloys. It has been shown that preliminary heating of specimens in the course of their laser-treatment increases the depth of the modified layer over the whole zone of treatment and improves the uniformity of distribution of reinforcing SiC particles; however, because of turbulence in the melt there is observed some non-uniformity of distribution of SiC particles in the modified layer. It is found that in the interaction of Al melt with SiC particles there forms plates of Al4C3 carbide at the interface, these plates grow mainly co-axially to the orientations of SiC crystals in the direction to the melt. Besides, in the matrix there takes place partial dissolution of SiC with formation of needle-shaped Al4C3 carbides. During the modification of surfaces of these alloys, in the case of increased concentration of silicium in the melt there is also observed inclusion of pure silicium. Besides, there is also possible the diffusion of aluminium into thin near-surface layer of silicium carbide, the layer separates from SiC crystal (phenomenon of ply separation) when the concentration of aluminium reaches a value of 3–5 %. It is established that the abrasive wear resistance of the non-modified AD35 alloy, which is determined according to the method of rigid abrasive wheel, is by 30–45 % higher than that of B95 alloy. In this case, the deterioration (wear-and-tear) proceeds according to the following two mechanisms: (1) by cutting and (2) by adhesive grafting between the abrasive wheel and the aluminium alloy by tearing out alloy particles from the surface. Optimal regimes of laser reinforcement of surfaces of aluminium alloy by means of fine SiC particles have been determined in this paper; this enabled us to increase 40–70 times the wear resistance of aluminium alloys in comparison with non-modified alloys when they are subjected to friction by rigidly fixed abrasive particles. The same reinforcement almost two times increases the wear resistance in dry reversive friction, and it increases the wear resistance only by 10–25 % in wearing by loose abrasive particles.
Keywords: surface characteristics; aluminium alloy; composite layer; radiation zone; diffusion; inhomogeneity; wear resistance; friction; laser reinforcement